Role of anti-mullerian hormone as a diagnostic tool for polycystic ovary syndrome - Singh, Shakun; Firdaus, Arshiya; Choudhary, Rachna; Dhama, Vandana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: PCOS has been recognized as the most frequent endocrinopathy among reproductive aged women. This study has been done to determine whether the measurement of serum AMH can be used to diagnose PCOS and as a tool to predict the prognosis of PCOS. Methods: This was a prospective case control study on a woman attending gynae OPD of LLRM Medical College, Meerut, from May 2018 to June 2019. Study comprised of 50 women diagnosed with PCOS using Rotterdam criteria and 50 controls. Clinical data were collected including history, oligomenorrhea, hirsutism, examination included BMI, FG score and blood investigations including serum FSH, LH, TSH, prolactin, estradiol and serum AMH level. USG was done for all women. Results: Both PCOS cases and controls were matched for age and BMI. Mean level of AMH in PCOS cases and controls was 7.1096 and 2.423 respectively, AMH was two to three times higher in women with PCOS than controls which was statistically significant (p<0.05). Most frequent phenotype of PCOS in this study was phenotype A (48%). Highest mean level of AMH was also found in phenotype A (OA+HA+PCOM), thus reflecting the severity of PCOS. Maximum diagnostic potential for PCOS was at cut off 4.22 ng/ml with sensitivity of 92.5% and specificity of 100%. Conclusions: AMH level can be used as diagnostic and prognostic modalities in PCOS. AMH value rises when hyperandrogenism is present therefore serum AMH levels also reflect the phenotype of PCOS and severity of PCOS.